Universal Health Coverage for Antiretroviral Treatment: A Review - Aklilu Endalamaw; Charles F Gilks; Fentie Ambaw; Tesfa Dejenie Habtewold; Yibeltal Assefa (MDPI AG, 2022)
Universal health coverage is essential for the progress to end threats of the acquired immunodeficiency syndrome epidemic. The current review assesses the publication rate, strategies and barriers for antiretroviral therapy (ART) coverage, equity, quality of care, and financial protection. We searched Web of Science, PubMed, and Google Scholar. Of the available articles, 43.13% were on ART coverage, 40.28% were on financial protection, 10.43% were on quality of care, and 6.16% were on equity. A lack of ART, fear of unwanted disclosure, lack of transportation, unaffordable health care costs, long waiting time to receive care, and poverty were barriers to ART coverage. Catastrophic health care costs were higher among individuals who were living in rural settings, walked greater distances to reach health care institutions, had a lower socioeconomic status, and were immunocompromised. There were challenges to the provision of quality of care, including health care providers' inadequate salary, high workload and inadequate health workforce, inappropriate infrastructure, lack of training opportunities, unclear division of responsibility, and the presence of strict auditing. In conclusion, ART coverage was below the global average, and key populations were disproportionally less covered with ART in most countries. Huge catastrophic health expenditures were observed. UHC contexts of ART will be improved by reaching people with poor socioeconomic status, delivering appropriate services, establishing a proper health workforce and service stewardship.